"Contributing factors of postgraduate enrolment" the case of Universiti Teknologi Petronas (UTP) / Mohammad Nizar Mat Nor and Mohd Zairee Shah Mohd Shah - Mat Nor, Mohammad Nizar; Mohd Shah, Mohd Zairee Shah (2008)
Nowadays paper qualification and working experience are among the great expectations from employers. Employees with a first degree qualification found it is inadequate for them to achieve higher career prospect and therefore postgraduate education serves as a mean to stimulate their minds, and enables them to learn new skills and acquire new knowledge. Postgraduate enrolment in a university is one of the main elements that reflect the university's reputation. The government through the Minister of Higher Education is focusing more on postgraduate education since the wide ranging benefits of postgraduate education has becoming a concern among the graduates and also working professionals. For an individual context, it may contribute in gaining notable financial returns as well as personal and intellectual benefits. For society, well-educated and highly trained professionals contribute to economic and technological development. This study aims to identify the interest of people to further their postgraduate study at UTP by looking at the factors which contribute to the university's postgraduate enrolment. The methodology applied in this study is a survey questionnaire whereby the population of respondents consists of the final year undergraduate students, postgraduate students as well as the working professional. At the end of this study, the findings and recommendation are based on the categories of the questionnaires such as financial aspect, career prospect, curriculum, R&D activities and supervisor's role. The findings will benefit the university's planning in conducting their postgraduate studies.